Culture- and quantitative IS900 real-time PCR-based analysis of the persistence of Mycobacterium avium subsp. paratuberculosis in a controlled dairy cow farm environment - Moravkova, M; Babak, V; Kralova, A; Pavlik, I; Slana, I (Applied and environmental microbiology, 2012)
The aim of this study was to monitor the persistence of Mycobacterium avium subsp. paratuberculosis in environmental samples taken from a Holstein farm with a long history of clinical paratuberculosis. A herd of 606 head was eradicated, and mechanical cleaning and disinfection with chloramine B with ammonium (4%) was carried out on the farm; in the surrounding areas (on the field and field midden) lime was applied. Environmental samples were collected before and over a period of 24 months after destocking. Only one sample out of 48 (2%) examined on the farm (originating from a waste pit and collected before destocking) was positive for M. avium subsp. paratuberculosis by cultivation on solid medium (Herrold's egg yolk medium). The results using real-time quantitative PCR (qPCR) showed that a total of 81% of environmental samples with an average mean M. avium subsp. paratuberculosis cell number of 3.09 × 10(3) were positive for M. avium subsp. paratuberculosis before destocking compared to 43% with an average mean M. avium subsp. paratuberculosis cell number of 5.86 × 10(2) after 24 months. M. avium subsp. paratuberculosis-positive samples were detected in the cattle barn as well as in the calf barn and surrounding areas. M. avium subsp. paratuberculosis was detected from different matrices: floor and instrument scrapings, sediment, or scraping from watering troughs, waste pits, and cobwebs. M. avium subsp. paratuberculosis DNA was also detected in soil and plants collected on the field midden and the field 24 months after destocking. Although the proportion of positive samples decreased from 64% to 23% over time, the numbers of M. avium subsp. paratuberculosis cells were comparable.
Keywords: Plants; nemoci skotu; DNA bakterií; Paratuberculosis; bydlení zvířat; Bacteriological Techniques; Mycobacterium avium subsp. paratuberculosis; kvantitativní polymerázová řetězová reakce; hospodářská zvířata; zvířata; kontrola infekce; mikrobiologie životního prostředí; DNA, Bacterial; paratuberkulóza; Cattle; Cattle Diseases; Environmental Microbiology; Veterinary Medicine; Animals, Domestic; skot; DNA Transposable Elements; Real-Time Polymerase Chain Reaction; Animals; Infection Control; veterinární lékařství; rostliny; bakteriologické techniky; transpozibilní elementy DNA; Housing, Animal